TATA RUANG KOTA CIAMIS PASCAPERDAGANGAN DUNIA ABAD KE-19 – 20 - Saptono, Nanang (PANALUNGTIK, 2018)
The capital of Ciamis Regency has experienced several displacements. During the reign of Raden Adipati Aria Kusumadiningrat the development of the capital was encouraged to develop into a city. After the kulturstelsel era, many European capitalists invested in Ciamis. At the beginning of the 20th century economic infrastructure, especially the means of distribution of commodities is much needed. Building economic facilities have sprung up in several locations in Ciamis. Such conditions result in the development of the city. This study aims to get a picture of the spatial layout of Ciamis and the city development process. The research method applied descriptive research. Data collection is done through direct observation in the field and accompanied by the utilization of instrument in the form of ancient maps. In the area of Ciamis City there are still some old building objects that can be used as a spatial bookmark of the city. At a glance the city's development spontaneously, but visible on the basis of existing infrastructure, in the 20th century the city of Ciamis showed a planned city. The growth of Ciamis city is of course influenced by several factors including economic and geographical factors.Keywords: city, layout, planned, industrial area